The Role of the Merah Putih Village Cooperative in Improving the Community Economy in North Lombok Regency - Adi Purmanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Nusa Tenggara Province that has significant human resources (HR) and natural resources (SDA) potential. This potential is an important capital in supporting the economic development of rural communities through cooperatives. The Red and White Village/Sub-district Cooperative Program (KDKMP) is a strategic government policy to strengthen the people's economy, improve community welfare, and realize equitable distribution of village economic development. This study aims to analyze the role of the Red and White Village Cooperative in improving the community's economy in North Lombok Regency. The research method used is descriptive qualitative with data collection techniques through field observations, community interviews, literature studies, documentation, and document analysis related to village cooperatives. The results show that the Red and White Village Cooperative plays an important role in increasing community access to capital, developing micro, small, and medium enterprises (MSMEs), expanding the marketing of local products, and creating jobs for rural communities. In addition, the presence of productive-age human resources is a major supporting factor in the development of cooperatives in the agriculture, trade, tourism, and creative industry sectors. However, cooperative development still faces various challenges, such as poor management quality, limited digital literacy, limited business plan development skills, and increasingly fierce market competition. Therefore, a strategy is needed to strengthen cooperatives through human resource capacity building, management training, MSME mentoring, digital technology utilization, and government and private sector support to enable cooperatives to develop independently, professionally, and sustainably.